Performances Concatenated LDPC based STBC-OFDM System and MRC Receivers - Nejwa El Maammar; Seddik Bri; Jaouad Foshi (Institute of Advanced Engineering and Science, 2018)
This paper presents the bit error rate performance of the low density parity check (LDPC) with the concatenation of convolutional channel coding based orthogonal frequency-division-multiplexing (OFDM) using space time block coded (STBC). The OFDM wireless communication system incorporates 3/4-rated convolutional encoder under various digital modulations (BPSK, QPSK and QAM) over an additative white gaussian noise (AWGN) and fading (Raleigh and Rician) channels. At the receiving section of the simulated system, Maximum Ratio combining (MRC) channel equalization technique has been implemented to extract transmitted symbols without enhancing noise power.